If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 9 = 4x + -7 Reorder the terms: 9 + 12x = 4x + -7 Reorder the terms: 9 + 12x = -7 + 4x Solving 9 + 12x = -7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 9 + 12x + -4x = -7 + 4x + -4x Combine like terms: 12x + -4x = 8x 9 + 8x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 9 + 8x = -7 + 0 9 + 8x = -7 Add '-9' to each side of the equation. 9 + -9 + 8x = -7 + -9 Combine like terms: 9 + -9 = 0 0 + 8x = -7 + -9 8x = -7 + -9 Combine like terms: -7 + -9 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| 33n-72=324 | | 8.96=w/7 | | 4n-9=15 | | 4m+4.75=30.75 | | -(3)+8(4)= | | -3(x-7)=2x-5x-21 | | 3n-11=40 | | -7x=y-3 | | (3/4)y−12=12 | | (-7)-2(2)= | | 3/4y−12=12 | | (2)-2(-2)= | | 8+3n=20 | | 3a+4b=26 | | -4x-5=-49 | | 17/3x-622 | | 3n-15=13 | | 1+3y=2.5-1.875y | | (3)-2(4)= | | 6-6x=x+1 | | 3l=l+20 | | 3=v/3.75 | | 9h^2-4=0 | | 5n-9=1 | | 3j=j+20 | | 15x+5+60=22x+4 | | 5(-6)-7(-6)= | | 2+x/6=3/5+x/30 | | 6X-4+2X+32=180 | | 5(-5)-7(0)= | | 3z+7z=33z-8(2-6)+z(8888z-7999z) | | 4x=(6x-12) |